Rational Thinking and Intellectually Virtuous Thinking: Identical, Extensionally Equivalent, or Substantively Different? - Siegel, Harvey (Informal Logic, 2023)
(1) Is the rational person eo ipso intellectually virtuous? (2) Is the intellectually virtuous person eo ipso rational? In what follows I answer both questions in the negative.